Implementation of Physical Medical Record Storage System as the Basis for Integration with the Electronic Medical Record System (RME) - Sri Inti; Riska Faraswati; Nikmatul Firdaus; Futri Januarti Aspandi; Enjelita Rambu (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
In the digitalization era, transforming Hospital Information Systems presents challenges in managing physical medical records, including limited digital infrastructure, unprepared human resources, and difficulties integrating manual systems with digital technologies. These challenges pose risks to data accuracy, accessibility, and patient safety during the shift toward more efficient and secure digital systems. Purpose: This study aims to evaluate the storage and management system of physical medical records amid the digitalization process and identify barriers and potential integration with digital systems. Method: A qualitative approach was used through a case study in a regional public hospital. Data were collected via in-depth interviews, observations, and document analysis. Results: Findings indicate that hospitals still rely on physical medical records due to limited infrastructure, cybersecurity concerns, and insufficient staff training. About 65% of respondents identified patient data protection as a major issue, while limited training reduced the effectiveness of electronic system implementation. Implications: The findings emphasize the need to strengthen IT capacity and provide ongoing staff training, supported by budgets for infrastructure and skill development. Conclusion: Although digitalization is inevitable, physical medical records remain essential during the transition. Integration can be achieved through hybrid systems using technologies such as barcode scanning to enhance data accuracy, efficiency, and security.